2020
DOI: 10.3390/v13010035
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Role of Cholesterol in the Life Cycle of Alphaviruses

Abstract: Enveloped viruses rely on different lipid classes present in cell membranes to accomplish several steps of their life cycle in the host. Particularly for alphaviruses, a medically important group of arboviruses, which are part of the Togaviridae family, cholesterol seems to be a critical lipid exploited during infection, although its relevance may vary depending on which stage of the virus life cycle is under consideration and whether infection takes place in vertebrate or invertebrate hosts. In this review, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
(121 reference statements)
0
13
0
Order By: Relevance
“…Further elucidation of the latter and how it is modulated by viruses thus presents as important aspect of focus. After cholesterol-dependent steps in endocytosis, shuttling of the lipid within virus-containing endosomes further is important for the uncoating, and therefore for final cellular entry, of enveloped viruses, such as members of the Filoviridae family, IAV, HIV, SARS-CoV-2, and Alphaviruses ( Schroeder, 2010 ; Carette et al, 2011 ; Côté et al, 2011 ; Garcia-Dorival et al, 2020 ; Martyna et al, 2020 ; Sousa et al, 2020 ). This process is reported to be mediated via cholesterol-shuttling proteins, such as NPC1.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…Further elucidation of the latter and how it is modulated by viruses thus presents as important aspect of focus. After cholesterol-dependent steps in endocytosis, shuttling of the lipid within virus-containing endosomes further is important for the uncoating, and therefore for final cellular entry, of enveloped viruses, such as members of the Filoviridae family, IAV, HIV, SARS-CoV-2, and Alphaviruses ( Schroeder, 2010 ; Carette et al, 2011 ; Côté et al, 2011 ; Garcia-Dorival et al, 2020 ; Martyna et al, 2020 ; Sousa et al, 2020 ). This process is reported to be mediated via cholesterol-shuttling proteins, such as NPC1.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…Targeting the endolysosomal cholesterol environment could be harnessed as an avenue for broadly acting antiviral drug development. Viruses from different families like coronaviruses, influenza A virus, filoviruses like Ebola, arthropod-borne alphaviruses (Sousa et al, 2020) and flaviviruses (Pombo and Sanyal, 2018) require endosomal escape of the infecting virion through fusion of viral and cellular membranes in the endosomal compartment. Modulation of endolysosomal cholesterol levels may thus influence the rate of this fusion event.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different cholesterol levels in hosts generate different envelope cholesterol levels in alphaviruses ( 177 ). When compared with mayaro virus particles from mosquito cells, virus particle envelopes from vertebrate cells have higher cholesterol levels ( 178 ). In terms of coronaviruses, Simons et al found that although MHV- S protein was localized to the Golgi, that contained cholesterol and lipid rafts, the assembled and released of MHV is not associated with cholesterol ( 167 ).…”
Section: The Role Of Cholesterol Metabolism During the Coronavirus Li...mentioning
confidence: 99%